A case of severe Pembrolizumab-induced neutropenia. Issue 8 (September 2018) - Barbacki, Ariane; Maliha, Peter G.; Hudson, Marie; Small, David
Abstract : Immune checkpoint inhibitors have revolutionized cancer therapy. Given their mechanism of action, immune-related adverse events have been associated with their use. We present the first documented case of pembrolizumab-induced grade IV neutropenia. A 73-year-old women known for myositis, Crohn's disease, and hypothyroidism and diagnosed with PD-L1 positive stage IV pulmonary adenocarcinoma is treated with Pembrolizumab. She develops grade IV neutropenia 2 weeks after her second infusion. She is therefore hospitalized and treated initially with corticosteroids, granulocyte colony-stimulating factor, and intravenous immunoglobulins. Given the persistent neutropenia, cyclosporine was added, but quickly stopped owing to fever. The patient recovered her neutrophils 6.5 weeks after her initial Pembrolizumab infusion and 12 days after admission. She has been subsequently successfully tapered off steroids with no recurrence after 3 months of follow-up. This is the first case of grade IV neutropenia secondary to Pembrolizumab. This case is of particular interest given the patient's pre-existing autoimmune history. Treatment of severe neutropenia due to other PD1 inhibitors has generally consisted of steroids, granulocyte colony-stimulating factor, intravenous immunoglobulins, mycophenolate mofetil, cyclosporine A, and anti-thymocyte globulins – though the benefits of immunosuppression are not clear and may be harmful given the infectious risks. Large studies are required to clarify the spectrum and optimal management of immune-related adverse events and overall risk/benefits of immune checkpoint inhibitors in patients with pre-existing autoimmunity.